Новые и малоизвестные виды двукрылых подсемейства Sciophilinae (Diptera, Mycetophilidae) - Зайцев, А.И. (Вестник зоологии, 1984)
Acnemia hyrcanica sp. n., Ectrepesthoneura montana sp. n. and E. nigra sp. n. are described. A. hyrcanica differs from closely related species A. angusta A. Zaitzev by the shape of ventral process of gonocoxite and by gonostyle structure. E. montana and E. nigra differ from other Palearctic species of the genus Ectrepesthoneura En d. and from each other by genitalic armature characters. New data on the distribution of Neuratelia pullata Ostroverchova are given.